Gender gap in authorship within published orthodontic research. An observational study on evidence and time-trends over a decade. (15th June 2021) - Schumacher, Caterina; Eliades, Theodore; Koletsi, Despina
Summary: Aim: To assess the representation of female authors in senior and leading positions in orthodontic research publications, as well as the fraction of women participating in the publication reports, for over a decade. In addition, association of women representation in orthodontic research and characteristics such as journal of publication, year, study design/topic, and others, were sought. Materials and methods: Electronic search was performed within three major orthodontic journals, namely the European Journal of Orthodontics (EJO), the American Journal of Orthodontics and Dentofacial Orthopedics (AJODO), and the Angle Orthodontist (ANGLE) to identify all types of research articles published within two distinct year cohorts, the 2008–10 and the 2018–20. The outcomes of interest pertained to proportion of women in senior (last) and leading (first) position, and fraction of overall participation in the author list. Results: A total of 2539 articles were eligible for inclusion, with an overall number of contributing authors being 11 608, of which 34.4% were female. For seniority in authorship, 30.1% (312/1038) of the publications within 2018–20 were attributed to female authors, while 25.8% (388/1501) was identified in 2008–10. Publication timeline, geographic region, and thematic topic of publication were determined as significant predictors. For leading (first) authorship, the respective percentages were 44.7% (464/1038) within 2018–20, and 34.7% (521/1501) in 2008–10. Dissemination timeline, geographic region and journal of publication were identified by the multivariable analysis, as revealing evidence of association with female leading publication authorship. Overall, the median proportion of female authors within the author list was 33.0%. Conclusions: A gender gap related to Orthodontic research publications is persistent, with participation of women either as senior, or as leading authors, being suboptimal. Consistent efforts should be set in place, to facilitate more equal representation of women in research publishing, being supported by academia.